An Overview of Carbon Markets for Florida Forest Landowners - José R. Soto; Francisco J. Escobedo; Damian C. Adams (EDIS)
Payments for sequestering carbon in forests can be an important supplemental income source in the southern US which includes one-third of the contiguous US forest carbon stocks and supplies 16% of the world’s wood. It is difficult to understand the carbon market and certification options available to Florida forest landowners and the possible risks of participating in them. To address this need, UF/IFAS forest management specialists provide this overview of forest carbon markets in the United States as of 2014 and compare key features of the four major carbon offset certification options. This 9-page fact sheet was written by José R. Soto, Francisco J. Escobedo, and Damian C. Adams, and published by the UF Department of School of Forest Resources and Conservation, July 2014.